Akuntabilitas Pengelolaan Dana Desa dan Faktor Anteseden yang Mempengaruhinya - Dekeng Setyo Budiarto; Agesti Dwi Setyaningrum; Ratna Purnama Sari (Akademi Akuntansi YKPN Yogyakarta, 2020)
This research aims to test the influence between the competency of government staff in managing government assistance fund, organizational commitment, society participation, and internal control system on the accountability of government assistance fund management in the Bantul Regency. This research using the quantitive method with multiple linear regression for analyzing the data. The total sample used in the study is 147 respondents. The result shows that the competency of government staff in managing government assistance fund, society participation, and internal control system had a positive effect on the accountability of government assistance fund management. At the same time, commitment organization does no impact the accountability of government assistance fund management in Bantul Regency.